Correlation of Islamic Work Ethic to Islamic Job Happiness In BMT Employeess In Yogyakarta and Surrounding Areas - Wijiharta, Wijiharta (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2023)
The Yogyakarta Special Region is known as the poorest province in Indonesia, with a relatively low minimum wage value for DIY provincial employees. However, on the other hand, the DIY province is also one of the destinations for job seekers and has a high level of happiness. There are allegations that 'nrimo' culture affects the level of happiness. This study aims to determine the influence of Islamic Work Ethic on Islamic Job Happiness on employees in Yogyakarta. This research is categorized as quantitative research. Data collection was carried out on 192 BMT employees in the Yogyakarta area using a questionnaire instrument on the google form. The collected data is then analyzed using the Smart-PLS program. The results showed that Islamic Work Ethic is positively correlated with Spiritual Islamic Job Happiness (S-IJH), Psychological Islamic Job Happiness (P-IJH), Social Islamic Job Happiness (C-IJH) and Phisical Islamic Job Happiness (F-IJH). The strongest correlation is IWE to C-IJH which is indicated by a coefficient value of 0.637, followed by a correlation of IWE to P-IJH (0.581), F-IJH (0.572) and S-IJH (0.563). Thus, the improvement of Islamic Work Ethic will increase Islamic Job Happiness for BMT employees in Yogyakarta and surrounding areas. Companies are advised to increase awareness of Islamic work ethics as an effort to increase the happiness of Islamic work of BMT employees in the Yogyakarta area and its surroundings.